A Decontamination Process to Remove Metals and Stabilise Montreal Sewage Sludge - G. Mercier; J.F. Blais; F. Hammy; M. Lounes; J.L. Sasseville (The Scientific World Journal)
The Montreal Urban Community (MUC) treatment plant produces approximately 270 tons of dry sludge daily (tds/day) during physicochemical wastewater treatment. The sludges are burned and contribute to the greenhouse effect by producing atmospheric CO2. Moreover, the sludge emanates a nauseating odour during its thermal stabilisation and retains unpleasant odours for the part (25%) that is dried and granulated. To solve this particular problem, the treatment plant authorities are currently evaluating an acidic chemical leaching (sulfuric or hydrochloric acid) process at a pH between 2 and 3, using an oxidizing agent such as ferric chloride or hydrogen peroxide (METIX-AC technology, patent pending; [20]). They could integrate it to a 70 tds/day granulated sludge production process. Verification of the application of METIX-AC technology was carried out in a pilot plant set up near the sludge production plant of the MUC. The tests showed that METIX-AC technology can be advantageously integrated to the process used at the MUC. The residual copper (274 ± 58 mg/kg) and cadmium (5.6 ± 2.9 mg/kg) concentrations in the treated sludge meet legislation standards. The results have also shown that odours have been significantly eliminated for the dewatered, decontaminated, and stabilized biosolids (> 97%) compared to the non-decontaminated biosolids. A high rate of odour elimination also was obtained for the liquid leached biosolids (> 93%), compared to the untreated liquid biosolids. The fertilising value (N and P) is well preserved by the METIX-AC process. Dissolved organic carbon measurements have showed that little organic matter is brought in solution during the treatment. In fact, the average concentration of dissolved organic carbon measured in the treated liquid phase is 966 ± 352 mg/l, whereas it is 1190 ± 325 mg/l in untreated sludge. The treated sludge was first conditioned with an organic polymer and a coagulant aid. It was successfully dewatered with various dehydration equipments (filter press, rotary press, centrifuge).